Analisis Pengaruh Kemiringan dan Bentuk Dasar Fishway Terhadap Rasio Perpindahan Sidat (Anguilla bicolor, sp) - Yusuf, Maulana; Wahono, Endro Prasetyo; Kusumastuti, Dyah Indriana; Tugiono, Subuh (Universitas Lampung, 2021)
The construction of a transverse structure on a river such as a dam and weir needs to pay attention to environmental factors and the surrounding ecosystem, especially for the ecosystem in the river. Therefore, it is necessary to build a fishway or fish in the transverse river structure so that the river ecosystem which has migration characteristics from upstream to downstream or vice versa is not disturbed because the migration route is blocked. This is the background of the author in taking the title of the thesis Analysis of the Effect of Slope and Basic Shape of Fishway on the Eel Movement Ratio (Anguilla bicolor, sp). The results of this study indicate that eels are nocturnal or active at night. Eel activity most often occurs at a fishway angle of 30 ° by testing using a 0.5 inch pvc pipe foothold type, while the lowest activity occurs at a 35 ° fishway tilt angle by testing using a 1 inch pvc pipe foothold type. The most effective slope based on the test results is at a slope angle of 30 ° but for a slope of 50 ° it can still be said to be effective because the activity ratio shows almost double the activity. Keywords: Fishway, Footing Type, Eel Activity